(untitled) (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
The development of digital technology and the increasing psychological pressures on modern society demand innovation in mental health practices. Hybrid Art Therapy Models, which combine art, mindfulness, and digital technology, emerged as a holistic approach to supporting mental well-being. This study uses the literature review method by examining scientific articles, books, and proceedings related to hybrid art therapy published in the period 2015–2025. The study process includes topic identification, literature search, selection based on relevance, data extraction, thematic analysis, and synthesis of results. The results of the study show that the hybrid art therapy model is effective in improving emotional expression, emotion regulation, self-awareness, and therapy participant involvement. Digital technologies, such as interactive apps, virtual reality, and online platforms, provide flexibility, inclusivity, and immersive experiences, while mindfulness deepens self-reflection in the creative process. This model is relevant for a variety of contexts, including education, mental health clinics, and community programs. However, its implementation faces challenges in the form of limited access to technology, training needs for therapists, and ethical and privacy issues. This study concludes that hybrid art therapy offers an innovative, creative, and adaptive approach to holistic healing, as well as being the basis for the development of further research in the field of mental health